Faktor yang Mempengaruhi Nilai Perusahaan dengan Moderasi Ukuran Perusahaan pada Sektor Healthcare di Bursa Efek Indonesia - Syahniar, Emiliana Nisa; Wikartika, Ira (Ekonomis: Journal of Economics and Business, 2024)
Company value is used to assess the importance of a company from the point of view of various parties, such as investors who are concerned with the valuation of a company through its share price. The high value of the company shows that the company is in a prosperous condition. The purpose of this research is to prove the overall effect of investment opportunity set, capital structure, and tax planning on company value with company size as a moderating variable in healthcare sector companies recorded on the Indonesia Stock Exchange for 2019-2023. The sampling technique in this research uses a purposive sampling technique and uses the Moderated Regression Analysis (MRA) method. The test results show that investment opportunity sets and tax planning have a significant positive contribution to firm value, capital structure has no contribution to firm value. Company size cannot moderate investment opportunity set and capital structure on company value, company size can moderate tax planning to increase company value in healthcare sector companies on the Indonesia Stock Exchange 2019-2023.